Analisis Kualitas Pelayanan dan Strategi Pengembangan Wisata Edukasi Sentulfresh Indonesia - Tanto Pratondo Utomo; Adam Jordan; Novita Herdiana; Wisnu Satyajaya (Universitas Mercu Buana, 2019)
Sentulfresh Indonesia Educational Tour can not avoid the effects of tight business competition, so it needs to improve the services quality continuously. The purpose of this research was to analyse level of services visitor satisfaction educational tour, and to formulate development strategies to increase the visitor satisfaction. This research was a descriptive study with qualitative and quantitative data. Qualitative data were obtained by in-depth interviews, whereas quantitative data were acquired using questionnaires of development strategic and level of service to analyzed by Servqual method. The internal and external environments were analyzed, followed by SWOT analysis. The result was used as data to formulate strategies followed by QSP) test to sequence priorities of the chosen strategies as strategy development of educational tour of Sentulfresh Indonesia. The result stated that the quality of service at the educational tour of Sentulfresh Indonesia has not meet the needs and desires of visitor. Based on SWOT analysis shows that the score of IFE was 2.743 and EFE was 2.430. The priority of alternative strategies based on QSPM test was Realizing the development of facilities on remaining land accompanied by repair and improvements to existing facilities (TAS = 6.620).